Meta‐analysis of echocardiographic quantification of left ventricular filling pressure. (23rd November 2020) - Jones, Rachel; Varian, Frances; Alabed, Samer; Morris, Paul; Rothman, Alexander; Swift, Andrew J.; Lewis, Nigel; Kyriacou, Andreas; Wild, James M.; Al‐Mohammad, Abdallah; Zhong, Liang; Dastidar, Amardeep; et al.
Abstract: Aims: The clinical reliability of echocardiographic surrogate markers of left ventricular filling pressures (LVFPs) across different cardiovascular pathologies remains unanswered. The main objective was to evaluate the evidence of how effectively different echocardiographic indices estimate true LVFP. Methods and results: Design: this is a systematic review and meta‐analysis. Data source: Scopus, PubMed and Embase. Eligibility criteria for selecting studies were those that used echocardiography to predict or estimate pulmonary capillary wedge pressure or left ventricular end‐diastolic pressures. Twenty‐seven studies met criteria. Only eight studies (30%) reported both correlation coefficient and bias between non‐invasive and invasively measured LVFPs. The majority of studies (74%) recorded invasive pulmonary capillary wedge pressure as a surrogate for left ventricular end‐diastolic pressures. The pooled correlation coefficient overall was r  = 0.69 [95% confidence interval (CI) 0.63–0.75, P  < 0.01]. Evaluation by cohort demonstrated varying association: heart failure with preserved ejection fraction (11 studies, n  = 575, r  = 0.59, 95% CI 0.53–0.64) and heart failure with reduced ejection fraction (8 studies, n  = 381, r  = 0.67, 95% CI 0.61–0.72). Conclusions: Echocardiographic indices show moderate pooled association to invasively measured LVFP; however, this varies widely with disease state. In heart failure with preserved ejection fraction, no single echocardiography‐based metric offers a reliable estimate. In heart failure with reduced ejection fraction, mitral inflow‐derived indices (E/e′, E/A, E/Vp, and EDcT) have reasonable clinical applicability. While an integrated approach of several echocardiographic metrics provides the most promise for estimating LVFP reliably, such strategies need further validation in larger, patient‐specific studies.